National Consumers' League records - National Consumers' League
Correspondence, memoranda, minutes, reports, speeches, project and program files, legal files, scrapbooks, printed material, miscellany, and other records relating to the league's efforts towards reform in public health, consumer protection, public welfare, and fair labor standards. Topics include child labor, the Equal Rights Amendment, the Fair Labor Standards Act, migratory labor, the National Council on Agricultural Life and Labor, social security, and wage and hour standards. Includes material relating to the activities of chartered local and state leagues. Prominent persons represented in the records include Grace Abbott, Mary Anderson, Newton Diehl Baker, Elizabeth Brandeis, Eveline Mabel Richardson Burns, John Rogers Commons, Mabel Cory Costigan, Molly Dewson, Paul Howard Douglas, Josephine Clara Goldmark, Pauline Dorothea Goldmark, Eleanor M. Hadley, Alice Hamilton, Dorothy Smith McAllister, Esther Peterson, Frances Perkins, Jeannette Rankin, Josephine A. Roche, John Augustine Ryan, John Gilbert Winant, Edwin E. Witte, Florence Richardson Wyckoff, and Susanna P. Zwemer.
Microfilm edition available, in part
In part, photocopies and transcripts.
Microfilm produced from original papers on radium poisoning.
Private
Library of Congress Prints and Photographs Division.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Keywords: Abbott, Grace, -- 1878-1939.; Anderson, Mary, -- 1872-1964.; Baker, Newton Diehl, -- 1871-1937.; Berry, Raymond H; Raushenbush, Elizabeth Brandeis; Burns, Eveline M. -- 1900-1985.; Commons, John R. -- 1862-1945.; Costigan, Mabel Cory, -- approximately 1873-1951.; Dewson, Molly, -- 1874-1962.; Douglas, Paul H. -- 1892-1976; Goldmark, Josephine, -- 1877-1950.; Goldmark, Pauline, -- 1874-1962.; Hadley, Eleanor M; Hamilton, Alice, -- 1869-1970.; McAllister, Dorothy Smith, -- 1899-1983.; Peterson, Esther, -- 1906-1997.; Perkins, Frances, -- 1880-1965.; Rankin, Jeannette, -- 1880-1973.; Roche, Josephine A. -- 1886-1976.; Ryan, John A. -- 1869-1945.; Winant, John G. -- 1889-1947.; Witte, Edwin E. -- 1887-1960.; Wyckoff, Florence, -- 1905-1983.; Zwemer, Susanna P. -- 1895-1992.; United States; National Council on Agricultural Life and Labor (U.S.); Child labor; Consumers; Consumers' leagues; Equal rights amendments; Hours of labor; Migrant labor; Public health; Public welfare; Reformers; Social security -- United States; Wages; Working class -- Law and legislation; Constitutional amendments -- United States